A novel Lipidoid-MicroRNA formulation promotes calvarial bone regeneration. (September 2018) - Sui, Lei; Wang, Ming; Han, Qianqian; Yu, Liming; Zhang, Lan; Zheng, Leilei; Lian, Junxiang; Zhang, Jin; Valverde, Paloma; Xu, Qiaobing; Tu, Qisheng; Chen, Jake
Abstract: Specific microRNAs (miRs) and the Wnt signaling pathway play critical roles in regulating bone development and homeostasis. Our previous studies revealed the ability of miR-335-5p to promote osteogenic differentiation by downregulating Wnt antagonist Dickkopf-1 (DKK1). The purpose of this study was to use nano-materials to efficiently deliver miR-335-5p into osteogenic cells for tissue engineering applications. We synthesized and screened a library of 12 candidate nano-lipidoids，of which L8 was identified as the preferred biodegradable lipidoid for miRNA molecule delivery into cells. We then investigated whether a lipidoid-miRNA formulation of miR-335-5-p (LMF-335) could successfully deliver miR-335-5-p into cells to promote osteogenesis in vitro and calvarial bone healing in vivo . Transfection of C3H10T1/2 cells and bone marrow stromal cells (BMSCs) with LMF-335 led to decreased expression of DKK1 and increased expression of the key osteogenic genes. LMF-335 and LMF-335-transfected BMSCs were then used in combination with silk scaffolds to evaluate healing of critical-size calvarial bone defects in mice. The results revealed significant new bone formation in the defects in LMF-335 groups as compared with control groups. In conclusion, this first report supports the notion that lipidoid delivery of miRNA can be used to induce osteogenic differentiation of stem cells and bone regeneration. Graphical abstract: Image 1